Integrasi Nilai-Nilai Ajaran Lokal Kaharingan Dalam Pembelajaran Pendidikan Agama Hindu - Ni Wayan Gateri; Nali Eka; I Gede Dharman Gunawan; I Ketut Subagiasta; Bayu Trisnawan (Jurnal Penelitian Agama Hindu, 2026)
The implementation of Hindu religious education is guided by the curriculum established by the national government. However, there are variations, particularly in Central Kalimantan Province, as Hindu religious teachers integrate Hindu religious material with local Kaharingan teachings as a means of practicing their religion in their daily lives. This is necessary due to the diversity of traditions within the Hindu archipelago, thus minimizing factors that cause conflict and disintegration. The purpose of this study is to demonstrate the relevance and potential for integrating local Kaharingan values ​​into the Hindu religious education curriculum. It also aims to explore the values ​​of local Kaharingan wisdom in Hindu Religious Education learning. The method used in this study is a qualitative method, conducted through in-depth exploration at the research location. The results of this study show that the local Kaharingan teaching values ​​integrated into Hindu religious education learning include 1) Lime Sarahan teaching values ​​on the Panca Sradha topic. 2) Hindu Kaharingan ceremony values ​​on the Panca Yadnya topic, 3) Kandayu and Tandak teaching values ​​on the Dharma Gita topic, and 4) Pandehen teaching values ​​on the Dharma Wacana topic. The method of integrating local Kaharingan teaching values ​​in Hindu religious education learning uses practical methods, assignment methods, and methods that can be directly understood by students. It can be concluded that local Kaharingan teaching values ​​can be integrated into Hindu Religious Education learning. With the integration of local Kaharingan values ​​in Hindu religious education learning, not only can it increase students' sradha bhakti and justification of faith, but students can also practice and implement Kaharingan teachings in everyday life in society.